Smoking Behavior as a Social Influence of Teenagers in Association in Sungai Beliung Urban Village - Astari, Zuri (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
This research aims to find out how the social influence of teenagers in the social process influences the formation of smoking behavior in minors as a form of social influence in the Sungai Beliung District. Researchers tried to examine the smoking behavior orientation of minors which was determined to be the influence of teenage social interactions. This research is in the form of a case study and uses a qualitative approach with data collection techniques, namely interviews, observation and literature study. The results of the research show that smoking behavior by minors is starting to become more common nowadays. The widening influence of relationships and the environment makes teenagers follow this behavior. Initially, teenagers are influenced by their social friends and the community, especially those around their home environment, most of whom are smokers.